Index to measure the cost of the basic food basket in the cities of Lavras and Nepomuceno (Research, Society and Development, 2025)
The objective of this study was to collect the prices of the food items that make up the basic food basket defined by DIEESE in markets in the cities of Lavras and Nepomuceno, to create an accessible index to track the evolution of these prices over time. Additionally, the study aimed to analyze whether the price variation in the basic food basket in these cities follows the same behavior observed in the capitals of Region 1. Data was collected from March to December 2024. Simple arithmetic average, inflation, accumulated inflation, and the number of work hours required to purchase the basic food basket were calculated. Comparing the average prices of the basic food basket during the mentioned period in markets from Lavras and Nepomuceno with those of the capitals in Region 1, it was observed that Market 3, located in Nepomuceno, had the lowest average price (R$671.78), while the market in São Paulo had the highest average price (R$821.08). The least number of work hours needed by a salaried worker to purchase the basic food basket was in Market 3 (95.47 hours). Considering the accumulated price index of the basic food basket in the Brazilian capitals of Region 1 and in the cities of Lavras and Nepomuceno, it was concluded that Market 1 recorded the highest accumulated price increase (12.62%) and Market 4 the lowest (-13.50%). Overall, the creation of an index to monitor such changes will allow the population covered in this study to have a distinct source of information regarding basic food basket data.